Formulasi Strategi Rumah Sakit Tentara dr. Soedjono Magelang - , Nawang Diani, SP, Dr. Budi Santoso, M.Bus ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Army Hospital dr. Soedjono Magelang is a hospital under the auspices of the army where their duty is to provide services to members of the army, civil servants and their families and also serve the general public health. In the face of competition and service needs in the health sector, the hospitals need appropriate strategies accordingly. This study aims to find out the Strength